Perception of dental faculty and student regarding class attendance and final performance - Sudhir S Rawlani; Shivlal M Rawlani; Vidya Lohe; Rahul Bhowate; Monika Rawlani Khubchandani; Rakhi Chandak (Wolters Kluwer Medknow Publications, 2018)
AIM: The aim of this study was to assess the impact of lecture attendance on the academic performance of 3rd BDS students at the DMIMS-U, Sawangi (M), Wardha. This project investigated and correlated the difference between faculty and student perceptions regarding attendance and final performance, including factors thought to influence student attendance. MATERIALS AND METHODS: Participants from a single university were included in the present retrospective observational study. The study was conducted in April 2016; 77 3rd BDS students (2012 Batch) and teaching staff of SPDC willing to voluntarily participate were included and divided into two groups such as Group A and Group B. Student and faculty perceptions were obtained using Likert scale having 15 closed-ended and 3 open-ended questions. Questioner was made related to factors affecting the attendance in class, type of source available for study, awareness about topic, and faculty approach. Comparison between perception of students and faculty regarding attendance and final performance was done using Mann-Whitney U-test. P < 0.05 was considered statistically significant. RESULTS: Quantitative analyses revealed significant differences between faculty and student perceptions on most of the project variables. Qualitative analyses reinforced those findings and suggested that faculty misunderstood what factors actually influence student attendance. The results suggest that there is a substantial disconnect between faculty and student perceptions regarding the importance of class attendance and highlighted areas for faculty to influence student attendance. CONCLUSION: Motivation is the major factor causing students to attend the lectures. Unfortunately, not all students are motivated to study and learn. New styles of teaching may need to be looked into. This needs to be further investigated on large sample size.